The Realization of Sports Intelligence Based on the Perspective of Students' Physical Fitness. Issue 4 (August 2021) - Zhang, Lingzhi; Wen, Meiling; Huang, Jing
Abstract: Intelligent technology is widely used in all aspects of life. The use of modern information technology to promote the development of sports intelligence to improve the physical health of students is an important way to reform school sports. As the development of school sports is facing problems such as insufficient attention and insufficient teachers, it is recommended to establish a dynamic monitoring system of student physique, school sports teaching and competition training management mechanism, construct a school sports culture network platform, and build a "cloud" by means of network technology such as big data. "Platform sports education new model and other paths to achieve the intelligent development of school sports.